ROLE OF CALCIUM, VITAMIN D AND VITAMIN D RECEPTORS IN PATHOGENESIS OF THEILERIOSIS IN CATTLE - Raheela Akhtar; Khurram Khan; Mehwish Naseer; Beenish Zahid; Uzma Farid Durrani (Journal of Animal and Plant Sciences, 2024)
The present study was conducted to examine the levels of calcium, vitamin D and Vitamin D receptor (VDR) in naturally-infected cattle with bovine theileriosis for understanding their role in the pathogenesis of the disease. A total of 100 cattle were selected, based on clinical signs in three districts of Punjab, Pakistan. Fifteen healthy animals were kept as negative controls. Blood samples were collected in EDTA containing vacutainer for Giemsa staining to examine the intra-erythrocytic forms of Theileria. Serum was collected in yellow top vacutainer for Vitamin D and calcium determination while plasma was also extracted for the determination of VDR levels from EDTA containing tubes. Giemsa staining showed 23% positive animals by microscopy while 32% of animals were positive by PCR. Levels of calcium, vitamin D, and VDR were very significantly (P<0.001) lower in Theileria affected animals in comparison to negative control. The results revealed that calcium, Vitamin D, and VDR might have a role in pathogensis of bovine theileriosis.
Keywords: Bovine Tropical Theileriosis; Calcium; Vitamin D; VDRs; T.annulata